A case study on the improvement of production line at the automotive industry - Mohammad Afiqzuddin Mohd Azan (School of Manufacturing Engineering, University Malaysia Perlis, 2016)
This project is on "a case study on the improvement of production line for side member at automotive industry". Traditionally operated industrial industries are facing problems like low productivity, longer production lead time, high rework and rejection, poor line balancing, low flexibility of style changeover. These problems were addressed in this study by the implementation of Six SIGMA tools like standard manufacturing line, single piece flow, work standardization, just in time production. Some of the key benefits entail production cycle time decreased, number of operators required to produce equal amount of production is decreased, rework level reduced by, production lead time comes down to one hour from two days, work in progress inventory stays at a maximum of 400 pieces per shift.